(untitled) (International journal of artificial intelligence, 2025)
This article explores international practices in promoting sustainable economic development through the implementation of resource-saving management systems. It delves into the theoretical foundations of sustainability, the practical implications of rational resource usage, and the comparative strategies employed by developed and developing nations in integrating eco-efficiency with economic growth. Emphasis is placed on policy mechanisms, technological innovations, institutional reforms, and market-based instruments that have proven effective in fostering a green economy. Through a detailed case-study-based approach, the article illustrates how countries such as Germany, Japan, Sweden, and South Korea have successfully transitioned toward sustainable development while maintaining economic competitiveness.